STUDIES OF THE ECONOMIC LEVEL OF DAMAGE OF THE POTATO MOTH, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - JARAMILLO-N., JORGE E.; ALVAREZ-A., ANGELA MARÍA; SALDARRIAGA-V., ALFREDO (Revista Colombiana de Entomología, 1989)
A study was carried out at "La Selva" Experiment Station, located at Rionegro (Antioquia, Colombia), during the second semester of 1986 and the first of 1987. The objective was to determine the parameters related to the economic level of damage caused by Phthorimaea operculella (Zeller). The leaf area damaged by the insect at the field was 6.29 ± 132 cm2 simulated percentages of 0, 25, 50 and 75% of defoliation at once and when the plant was 35, 55 and 75 days old, indicated that the levels above 25% affected the yield and the tuber quality. A regression analysis to measure the relationship between foliar damage and yield for each one of the crop ages studied and one to three insecticide applications showed the following results: For the 35 days old crop with one and three insecticide applications, the damage levels were 3.19 and 9.6 worms by the plant. For the 55 days old crop with one and three insecticide applications, the damage levels were 2.44 and 7.35 worms by the plant. An for the 75 days old crop the damage levels were 4.48 and 6.65 worms by plants, respectively.